Online ludic activities and their effectiveness in english language learning at Medalla Milagrosa Elementary School 2016 - Espinosa Cubilla, Anthony Davis (David, Panamá : UDELAS, 2016)
This research has a main goal; to offer some new advantages through the use of online ludic activities in order to develop the new student generation learning process; it will identify how students can learn english through different online activities, and the different current devices according with the technological landscape. Moreover, it provides to the teachers a gyude ti facukutate the second language acquisition to the digital natives or z generation, these new technological tools will make the learning process understandable and easier for these new students generations.
GENERAL INDEX DEDICATORY AKNOWLEDGMENTS GENERAL INDEX GRAPHICS INDEX INTRODUCTION CHAPTER I: THE RESEARCH PROBLEM CHAPTER II: THEORETICAL FRAMEWORK 2.1. Online ludic activities 2.1.1. Online ludic activities concept 2.1.2. Advantages of online ludic activities 2.1.3. Advices for the use of on line ludic activities 2.1.4. Online ludic activities to develop the four linguistic skills 2.2. Supporting theories for online ludic activities 2.2.1. Piagget's cognitive theory 2.2.2. Groos pre-exercise theory 2.3. Digital natives and the challenging digital world 2.3.1. Digital natie concept 2.3.2. How learners have changed in their learning process 2.3.3. Role of the teacher in the digital world 2.4. Relationship among computer and learning 2.4.1. Cmputers and learning 2.4.2. Blended learning 2.4.3. Gamification CHAPTER III: METHODOLOGICAL ASPECTS CHAPTER IV: ANALYSIS AND RESULTS CONCLUSIONS RECOMMENDATIONS BIBLIOGRAPHY
Incluye General Index
Documento presentado para optar por el Título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; ENGLISH -- TESIS DE LICENCIATURA -- ACTIVITIES; ENGLISH -- TESIS DE LICENCIATURA -- LANGUAGE; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE INGLÉS; LICENCIA EN DOCENCIA EN INGLÉS; MEDALLA MILAGROSA ELEMENTARY SCHOOL